Co-existence of Functionally Different Vesicular Neurotransmitter Transporters - Münster-Wandowski, Agnieszka; Zander, Johannes-Friedrich; Richter, Karin; Ahnert-Hilger, Gudrun (Frontiers in Synaptic Neuroscience, 2016)
The vesicular transmitter transporters VGLUT, VGAT, VMAT2 and VAChT, define phenotype and physiological properties of neuronal subtypes. VGLUTs concentrate the excitatory amino acid glutamate, VGAT the inhibitory amino acid GABA, VMAT2 monoamines, and VAChT acetylcholine into synaptic vesicle (SV). Following membrane depolarization SV release their content into the synaptic cleft. A strict segregation of vesicular transporters is mandatory for the precise functioning of synaptic communication and of neuronal circuits. In the last years, evidence accumulates that subsets of neurons express more than one of these transporters leading to synaptic co-release of different and functionally opposing transmitters and modulation of synaptic plasticity. Synaptic co-existence of transporters may change during pathological scenarios in order to ameliorate misbalances in neuronal activity. In addition, evidence increases that transporters also co-exist on the same vesicle providing another layer of regulation. Generally, vesicular transmitter loading relies on an electrochemical gradient µH+ driven by the proton ATPase rendering the lumen of the vesicle with respect to the cytosol positive () and acidic (pH). While the activity of VGLUT mainly depends on the component, VMAT, VGAT and VAChT work best at a high pH. Thus, a vesicular synergy of transporters depending on the combination may increase or decrease the filling of SV with the principal transmitter. We provide an overview on synaptic co-existence of vesicular transmitter transporters including changes in the excitatory/inhibitory balance under pathological conditions. Additionally, we discuss functional aspects of vesicular synergy of transmitter transporters.